Efficacy and Safety of Secukinumab in the Treatment of Axial Spondyloarthritis: Real-Life Data from TURKBIO Cohort - Gulle, Semih; Karakas, Ali; Can, Gercek; Senel, Soner; Capar, Sedat; Dalkilic, Huseyin Ediz; Sari, Ismail (Wiley, 2022)
[Abstract Not Available]
Annual Meeting of the American-College-of-Rheumatology (ACR) -- NOV 10-14, 2022 -- Philadelphia, PA